The relationship between manufacturing output, foreign direct investment, trade openness and labor productivity / Nurul Asyikin Idris - Idris, Nurul Asyikin (2007)
This study is to examine the relationship between manufacturing with labor productivity, trade openness and foreign direct investment in Malaysia. This study use data on manufacturing output, value-added per worker, trade balance and GDP from the period 1990 - 2006. The dependent variable for this study is manufacturing while independent variable are labor productivity, trade openness and foreign direct investment. The multiple linear regression will be use to test the relationship. This study is conducted by using SPSS to find the Coefficient of Determination or Adjusted R-Square, F-statistic or ANOVA and Multiple Linear Regression. This software important to find the relationship between variables whether it give negative or positive relationship. Based on the analysis, only trade openness and labor productivity give positive relationship on manufacturing output. Meanwhile, FDI give negative relationship on manufacturing output. Even though it give negative relationship, it still had relationship on manufacturing output but little effect maybe due to economy condition.